Addiction on Technology toward Kids and Teenagers Development - Abdul Aziz, Sarah Adlina (Journal of Computing Technologies and Creative Content, 2019)
Technology is the important things in daily life that could not be separated as it has become one of the needs to everyone. Every day, there were new technology has been developed and it is growing fast from day to day which has driven to the largest factor of the global development. Technology also has created the gap between the generation due to the fact that people of all ages are really comfortable with the technology even it has separated the young and old people. The advancement of the technology also affects the development and manners of many people in positive and negative ways which is somehow give bad impact to the country’s progress. Technology is the important things in daily life that could not be separated as it has become one of the needs to everyone. Every day, there were new technology has been developed and it is growing fast from day to day which has driven to the largest factor of the global development. Technology also has created the gap between the generation due to the fact that people of all ages are really comfortable with the technology even it has separated the young and old people. The advancement of the technology also affects the development and manners of many people in positive and negative ways which is somehow give bad impact to the country’s progress.